2014
DOI: 10.3389/fphar.2014.00242
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ signaling is required for mediating EETs protective effects in neonatal cardiomyocytes exposed to LPS

Abstract: Lipopolysaccharide (LPS) is a bacterial wall endotoxin producing many pathophysiological conditions including myocardial inflammation leading to cardiotoxicity. Epoxyeicosatrienoic acids (EETs) are biologically active metabolites of arachidonic acids capable of activating protective cellular pathways in response to stress stimuli. EETs evoke a plethora of pathways limiting impairments of cellular structures, reducing cell death, and promoting anti-inflammatory reactions in various cell types. Considering EETs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…In our previous studies, we demonstrated LPS triggered an inflammatory response in cardiomyocytes, which was partially associated with caspase activation and cell death. 18 , 19 As expected, treatment with LPS promoted significant upregulation of NF- κ B DNA-binding activity initiating an inflammatory cascade ( Figure 3a ). Consistent with this observation, LPS caused release of the major pro-inflammatory cytokine TNF α from HL-1 cells ( Figure 3b ).…”
Section: Resultssupporting
confidence: 72%
“…In our previous studies, we demonstrated LPS triggered an inflammatory response in cardiomyocytes, which was partially associated with caspase activation and cell death. 18 , 19 As expected, treatment with LPS promoted significant upregulation of NF- κ B DNA-binding activity initiating an inflammatory cascade ( Figure 3a ). Consistent with this observation, LPS caused release of the major pro-inflammatory cytokine TNF α from HL-1 cells ( Figure 3b ).…”
Section: Resultssupporting
confidence: 72%
“…An important element of the mitochondrial quality is the biogenesis of mitochondrial proteins. EETs are recognized agonists for peroxisome proliferator-activated receptors (PPARs) [ 36 , 46 ], which play a significant role in promoting expression of several mitochondrial proteins [ 47 , 48 ] Recently, Wang et al reported that 14,15-EET induced mitochondrial biogenesis in cortical neuronal cells via activation of cAMP-response element binding protein (CREB), which in turn activated the peroxisome proliferator-activated receptor gamma-coactivator 1 (PGC1) [ 49 ]. In order to investigate the involvement of mitochondrial biogenesis in the protective effect of EETs in HL-1 cardiac cells, we assessed several regulators of mitochondrial biogenesis following 6 and 24 hours of starvation.…”
Section: Resultsmentioning
confidence: 99%
“…To measure cellular energy levels, we used a bioluminescence-based kit (Sigma–Aldrich, Oakville, ON, CAN) to assay the ratio between ATP and ADP in HL-1 cells as described previously [ 36 ]. Briefly, cells were cultured on a 96-well plate then treated accordingly to the starvation protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that EETs enhance cardiomyocyte cell survival via a protective cascade targeting the mitochondria (Katragadda et al, 2009 ; Batchu et al, 2012a ; Samokhvalov et al, 2013 , 2014 ). Emerging evidence suggests the cardioprotective effect of EETs is due to inhibition of mitochondrial damage.…”
Section: Introductionmentioning
confidence: 99%